2006
DOI: 10.1182/blood-2006-05-021188
|View full text |Cite
|
Sign up to set email alerts
|

T-lymphoid, megakaryocyte, and granulocyte development are sensitive to decreases in CBFβ dosage.

Abstract: The family of core-binding factors includes the DNA-binding subunits Runx1-3 and their common non-DNA-binding partner CBF␤. We examined the collective role of core-binding factors in hematopoiesis with a hypomorphic Cbfb allelic series. Reducing CBF␤ levels by 3-or 6-fold caused abnormalities in bone development, megakaryocytes, granulocytes, and T cells. T-cell development was very sensitive to an incremental reduction of CBF␤ levels: mature thymocytes were decreased in number upon a 3-fold reduction in CBF␤ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
62
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(66 citation statements)
references
References 54 publications
(96 reference statements)
4
62
0
Order By: Relevance
“…It is known that mice that lack CBF␤, a functional partner of AML1, phenotypically recapitulate AML1 knockout mice, showing total loss of definitive hematopoiesis. A recent report using CBF␤ hypomorphic mice revealed that 15% of the wildtype level of CBF␤ is sufficient for emergence of definitive hematopoiesis (30). In this report, attenuated doses of CBF␤ between 15 and 30% of wild type cause expansion of hematopoietic stem/ progenitor cells in neonates, which return to normal when CBF␤ is restored up to the hemizygous level.…”
Section: Discussionmentioning
confidence: 61%
“…It is known that mice that lack CBF␤, a functional partner of AML1, phenotypically recapitulate AML1 knockout mice, showing total loss of definitive hematopoiesis. A recent report using CBF␤ hypomorphic mice revealed that 15% of the wildtype level of CBF␤ is sufficient for emergence of definitive hematopoiesis (30). In this report, attenuated doses of CBF␤ between 15 and 30% of wild type cause expansion of hematopoietic stem/ progenitor cells in neonates, which return to normal when CBF␤ is restored up to the hemizygous level.…”
Section: Discussionmentioning
confidence: 61%
“…RUNX-1-deficient megakaryocytes have hypolobulated nuclei, underdeveloped cytoplasm, low DNA ploidy, and enhanced replating activity in semisolid medium culture assays. Haploinsufficiency of CBF-␤ also perturbs megakaryopoiesis in mice (54). These findings indicate that RUNX-1/CBF-␤ is required for terminal megakaryocyte maturation.…”
mentioning
confidence: 64%
“…Because Runx transcription factors act in association with the structurally unrelated Cbf␤ protein (29), which participates in Runx-mediated CD4 repression (24,30), it was possible that Zbtb7b might antagonize Runx function by reducing the expression of endogenous Cbf␤. To address this possibility, we examined whether Zbtb7b would antagonize Runx3-mediated silencer activation in RLM-11 cells cotransfected with Cbf␤.…”
Section: ϫ4mentioning
confidence: 99%